Sex and Age Aspects in Patients Suffering From Out-Of-Hospital Cardiac Arrest: A Retrospective Analysis of 760 Consecutive Patients. Issue 18 (May 2016) - Piegeler, Tobias; Thoeni, Nils; Kaserer, Alexander; Brueesch, Martin; Sulser, Simon; Mueller, Stefan M.; Seifert, Burkhardt; Spahn, Donat R.; Ruetzler, Kurt
Abstract : Abstract: Cardiopulmonary resuscitation (CPR) is indicated in patients suffering from out-of-hospital cardiac arrest. Several studies suggest a sex- and age-based bias in the treatment of these patients. This particular bias may have a significant impact on the patient's outcome. However, the reasons for these findings are still unclear and discussed controversially. Therefore, the aim of this study was to retrospectively analyze treatment and out-of-hospital survival rates for potential sex- and age-based differences in patients requiring out-of-hospital CPR provided by an emergency physician in the city of Zurich, Switzerland. A total of 3961 consecutive patients (2003–2009) were included in this retrospective analysis to determine the frequency of out-of-hospital CPR and prehospital survival rate, and to identify potential sex- and age-based differences regarding survival and treatment of the patients. Seven hundred fifty-seven patients required CPR during the study period. Seventeen patients had to be excluded because of incomplete or inconclusive documentation, resulting in 743 patients (511 males, 229 females) undergoing further statistical analysis. Female patients were significantly older, compared with male patients (68 ± 18 [mean ± SD] vs 64 ± 18 years, P = .012). Men were resuscitated slightly more often than women (86.4% vs 82.1%). Overall out-of-hospital mortality rate was found to be 81.2% (492/632 patients) with no differences between sexes (82.1% for males vs 79% for females, odds ratio 1.039, 95% confidence interval 0.961–1.123). No sex differences were detected in out-of-hospital treatment, as assessed by the different medications administered, initial prehospital Glasgow Coma Scale, and prehospital suspected leading diagnosis. The data of our study demonstrate that there was no sex-based bias in treating patients requiring CPR in the prehospital setting in our physician-led emergency ambulance service.